Food preference factors among international students in a public university in Malaysia - Engin, Nurunnisa Kartal (2022)
Food preference is defined as liking or disliking of a food. However, preference of food is not a simple selection mechanism of one food over another. The selection of food is a long process. Studies among international students showed that students living away from home started to consume a reduced amount of vegetables and fruits and, eat more fast food, more sweet and salty snacks, and drink alcoholic beverages. However, literature is still limited regarding food-related issues among international students across the globe. While the number of international students has been increasing in Malaysia, understanding their food-related needs and emphasizing their issues becomes more significant. Therefore, this study aimed to determine factors influencing food preferences of international students in Universiti Putra Malaysia. In this cross-sectional study, 619 international students from selected faculties have completed the entire 20-minute online survey. The questionnaire consisted of seven different sections; socio-demographic characteristics, psychological factors, food environment, general acculturation, food choice motives, general nutrition knowledge and food preferences. Food preferences were measured by 77- item Food Preference Questionnaire (FPQ). Food items were selected to fall into six food group categories; 20 vegetable items,15 fruit items, 14 animal items, eight dairy items, eight snack items, 10 starch items. Pearson and Spearman Correlation, Kruskal-Wallis test, Mann Whitney U test and multiple linear regression were applied to the research objectives. Multiple linear regression results in this study showed that food availability (β=0.182, p<0.001) was for animal food preferences, price (β= 0.179, p<0.001) was for starchrelated food preferences, general acculturation (β= 0.156, p<0.001) was for dairy category food preferences, general nutrition knowledge about diet, disease and weight management (0.257, p<0.001) was for fruit food preferences, food neophobia (β= 0.132, p=0.001) was for snack-related food preferences and ethical concern (β= 0.265, p<0.001) was for vegetable preferences are the most significant contributors. In conclusion, this study indicated that food environment (availability, accessibility and affordability), food choice motives, general acculturation and, general nutrition knowledge emerged as prominent influencing factors towards food preferences among international students in Universiti Putra Malaysia. Some of the prominent factors can be enhanced with help of International Students' Association at Universiti Putra Malaysia (UPMISA) and UPM Student Affairs Division. For instance, during orientations, UPMISA could distribute explanatory maps that show where fresh food is found in and around the campus to improve the food environment in UPM. UPM Student Affairs Division could work with Department of Nutrition to prepare simple and educational leaflets about general nutrition knowledge especially for international students. Moreover, efforts are also being made by the streaming media (UPM campus radio) to introduce local foods and the ways of practical preparing methods for international students. Further study is needed to understand how the factors in this study influence other international students throughout Malaysia.